Development of Google Sites-Based Websites as A Learning Media for Indonesian Language in Elementary Schools to Enhance Pancasila Students Profiles - Sundari, Sri; Sudiyana, Benedictus; Subiyantoro, Singgih (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop Google Sites as a learning media for Indonesian language instruction to enhance the Pancasila Student Profile in elementary schools. The study employed a Research and Development (R&D) methodÂ with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects were elementary school teachers and students who utilized this web-based learning media. Data were collected through interviews and observations with respondents. The data analysis included qualitative methods, such as data reduction and presentation, as well as quantitative analysis, supported by data triangulation to compare findings from various sources. The research showed that 84.6% of respondents strongly agree, and 15.4% agree, that this Google Sites-based platform was effective in increasing student engagement and interest in learning Indonesian. This learning medium allows students to study independently, search for necessary materials flexibly, and access engaging and interactive learning resources, positively impacting their understanding and learning outcomes. Additionally, the media received a feasibility score of 3.75. The content and language feasibility score of 3.75 also indicates an enhancement in the characteristics of the Pancasila student profile. Features such as discussion forums, collaborative project assignments, and materials aligned with Pancasila values help students develop skills in collaboration, critical thinking, and national values. Students are encouraged to actively participate and collaborate with peers, fostering cooperation and responsibility.